HUBUNGAN HAFALAN ALQURAN DENGAN KECERDASAN SPIRITUAL (SQ) (Studi Analisis Terhadap Siswa Kelas XI di Mu’allimin PPI 45 Rahayu) - Salma Amalia Nurdini; Agung Mulyadin (Islamic Journal of Education, 2022)
The purpose of research are; (1) Explaining qurans memorize of XI students Mu’allimin PPI 45 Rahayu, (2) explaning spiritual intelligence (SQ) of XI students Mu’allimin PPI 45 Rahayu, (3) explaning isthere any relation between memorizing of quran dang spiritual intelligence (SQ) of XI students Mu’allimin PPI 45 Rahayu. The result of research that; (1) quran memorize of XI students Mu’allimin PPI 45 Rahayu was in sufficient category, in avarage value of 2,65 for partial analysis. That value is in interval 2,5-3,5, it menas the value was in sufficient category. (2) spiritual intelligence (SQ) of XI students Mu’allimin PPI 45 Rahayu is in sufficient category, in average value of partial analysis of 3,19. That value is in interval 2,5-3,5 and it means that value is categorized as sufficient. (3) as for correlation based on hypothesis test that t count = 7,20 > t table = 1,663. Therefor H0 was rejected and H1 was accepted, because there was a significant relation both of variables. As for correlation coefficient of 0.62 was in interval 0,600-0,799 including category of strong correlation.